2021
DOI: 10.1186/s12884-021-04276-5
|View full text |Cite
|
Sign up to set email alerts
|

Distance matters: barriers to antenatal care and safe childbirth in a migrant population on the Thailand-Myanmar border from 2007 to 2015, a pregnancy cohort study

Abstract: Background Antenatal care and skilled childbirth services are important interventions to improve maternal health and lower the risk of poor pregnancy outcomes and mortality. A growing body of literature has shown that geographic distance to clinics can be a disincentive towards seeking care during pregnancy. On the Thailand-Myanmar border antenatal clinics serving migrant populations have found high rates of loss to follow-up of 17.4%, but decades of civil conflict have made the underlying fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…However, we found that the increase in distance of mothers' homes to the nearest healthcare facility reduces women's ANC services uptake, especially in the rural areas. Our ndings corroborates with the ndings from other LMICs settings [31,32,[34][35][36][37][50][51][52][53][54]. There are several possible explanations for this in uence.…”
Section: Discussionsupporting
confidence: 91%
“…However, we found that the increase in distance of mothers' homes to the nearest healthcare facility reduces women's ANC services uptake, especially in the rural areas. Our ndings corroborates with the ndings from other LMICs settings [31,32,[34][35][36][37][50][51][52][53][54]. There are several possible explanations for this in uence.…”
Section: Discussionsupporting
confidence: 91%
“…Increased risk of NH in UGT1A1 � 6 was first reported in Japan over 20 years ago [29] and has been observed elsewhere in East Asian countries (Taiwan [30]; Malaysia [31]; Thailand [32]), although in certain contexts the increased risk in neonates with the mutation was only observed in association with large neonatal body weight loss [33]. NH which develops after discharge from birth centres in newborns with higher EGA and no obvious risk factors represents a clinical challenge in low resource settings and, in particular, in migrant populations where access and medical followup cannot be provided easily [34]. Levels of TSB observed in neonates homozygous for UGT1A1 � 6 at 48h (i.e.…”
Section: Plos Global Public Healthmentioning
confidence: 82%
“…Given the experience of the nurses and medics who have been working in SMRU SCBUs since their establishment, their reflections captured in FGDs lend a historical perspective to the qualitative findings. The narratives from women receiving SCBU care may be limited due to when they were collected, but they align with many of the issues related to coverage, acceptability, adoption, feasibility, and fidelity for maternal, neonatal, and infant care documented previously in this setting ( 23 , 46 , 76 , 78 ). Given that the original mixed methods design was intended to inform best SCBU practices for this setting, the qualitative findings have been kept as a valuable contribution to the continuous improvement process for SCBU care.…”
Section: Discussionmentioning
confidence: 82%
“…These communities provided readily accessible, unskilled labor to help fuel Thailand's local border economy and further its affluence relative to its western neighbor. This narrative contextualizes this study's findings, contrasting a refugee yet reachable population with a mobile, migrant one—both constrained by overlapping and nuanced externalities ( 40 , 41 , 52 , 54 , 75 ) that inform the adaptation, maintenance, and improvement of evidence-based provision of newborn care ( 12 , 21 , 25 , 39 , 42 , 44 , 46 , 51 , 76 78 ). Although a very specific setting, this study may provide insights to researchers, clinicians, and program managers promoting newborn health that are applicable to their context.…”
Section: Discussionmentioning
confidence: 89%